GAB1‐ABL1 fusions in tumors that have histologic overlap with NTRK‐rearranged spindle cell tumors. Issue 9 (10th June 2021) - Choo, Florence; Rakheja, Dinesh; Davis, Lara E.; Davare, Monika; Park, Jason Y.; Timmons, Charles F.; Neff, Tanaya; Beadling, Carol; Corless, Christopher L.; Davis, Jessica L.
Abstract: Fibroblastic spindle cell tumors are a heterogeneous group of rare soft tissue tumors that are increasingly recognized as associated with a variety of kinase gene fusions. We report two cases of GAB1‐ABL1 fusions in spindle cell tumors that histologically overlap with neurotrophic tyrosine receptor kinase ( NTRK )‐rearranged spindle cell tumors. The first case occurred in a 76‐year‐old female who had a large deep‐seated spindle cell tumor composed of monotonous ovoid to spindle cells in a background of thick stromal collagen bands with prominent hyalinized vessels and inconspicuous mitoses (<1/10 HPF). Immunohistochemical stains showed co‐expression of S100 and CD34. A GAB1‐ABL1 fusion was detected by whole transcriptome RNA sequencing. The patient had a partial response to imatinib. The second case was previously described as a solitary fibrous tumor, occurring in a 9‐year‐old female with a cellular spindle cell tumor with patchy CD34 immunoexpression but no expression of S100. Upon clinicopathologic re‐review, including anchored multiplex next‐generation sequencing, a GAB1‐ABL1 fusion was identified. In summary, we report the first two cases of spindle cell tumors with variable expression of CD34 and/or S100, driven by GAB1‐ABL1 gene fusions with histologic overlap with NTRK ‐rearranged spindle cell tumors, suggesting that ABL ‐fusions may also be oncogenic drivers within this spectrum of tumors. These cases highlight the evolving understanding of fibroblastic spindle cell tumor biology and the utility of sequencing in identifying a targetable alteration.